2016
DOI: 10.1016/j.vaccine.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional CD4 T-cells correlate with in vitro mycobacterial growth inhibition following Mycobacterium bovis BCG-vaccination of infants

Abstract: These data suggest that BCG vaccination of infants induces specific polyfunctional T-helper-1 and T-helper-17 responses and the ability, in the PBMC compartment, to inhibit the growth of mycobacteria in vitro. We also demonstrate that polyfunctional T-helper-1 cells may play a role in growth inhibition as evidenced by a significant correlation between the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 42 publications
6
64
1
Order By: Relevance
“…It is a heterogeneous field and a diverse range of assays have been proposed for both humans, mice and cattle 6 . Recently, there has been a move towards protocol harmonisation and standardisation in the field, including the publication of a murine MGIA protocol based on direct co-culturing of mouse splenocytes with BCG 13, 15, 18 , which we and others have used as foundation for murine as well as human PBMC based MGIA studies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a heterogeneous field and a diverse range of assays have been proposed for both humans, mice and cattle 6 . Recently, there has been a move towards protocol harmonisation and standardisation in the field, including the publication of a murine MGIA protocol based on direct co-culturing of mouse splenocytes with BCG 13, 15, 18 , which we and others have used as foundation for murine as well as human PBMC based MGIA studies 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Heparinized venous blood was obtained 4 months post-vaccination or from unvaccinated infants at an age-matched time point. This exploratory study was part of a larger study (11) and 4-month post-vaccination samples available were n  = 11, vaccinated infants; and n  = 10, unvaccinated infants for Luminex analysis and n  = 10 and n  = 8, respectively, for flow cytometry analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In infants vaccinated with BCG, a setting in which this vaccine is protective, polyfunctional CD4 ϩ T cells expressing IFN-␥, TNF-␣, and IL-2 correlate with in vitro mycobacterial growth inhibition (31). Previous studies in the murine model demonstrated a critical role of IL-17 in vaccine-induced immunity against TB and in protective immunity against hypervirulent M. tuberculosis infection (29,30).…”
Section: Discussionmentioning
confidence: 98%
“…Polyfunctional CD4 ϩ T cells, IL-17, and Th17 cells play roles in protection against TB (29)(30)(31). With a 12-week prime-boost interval, lung ( Fig.…”
Section: Immunogenicity Of Rlmiii/a30 As a Booster Vaccine In Bcg-primentioning
confidence: 99%